2001
DOI: 10.1152/ajprenal.2001.280.5.f860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water deprivation and hypertonic saline infusion on urinary AQP2 excretion in healthy humans

Abstract: Arginine vasopressin (AVP) mediates water transport in the renal collecting ducts by forming water channels of aquaporin-2 (AQP2) in the apical plasma membrane. AQP2 is excreted in human urine. We wanted to test the hypothesis that urinary excretion of AQP2 (u-AQP2) reflects the effect of AVP on the renal collecting ducts during water deprivation and hypertonic saline infusion in healthy subjects. Fifteen healthy subjects underwent a 24-h period of fluid restriction. Urine and blood samples were collected at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 19 publications
6
79
2
Order By: Relevance
“…However, both u-AQP2 and u-ENaC b increased significantly just as p-AVP, p-ANP, and pulse rate. The amount of ENaC b in urine is supposed to reflect the activity of sodium transport via the ENaCs, just as u-AQP2 reflects the functional status of the AQP2 water channels (6). Our analyses showed that the assay has a satisfactory reliability.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, both u-AQP2 and u-ENaC b increased significantly just as p-AVP, p-ANP, and pulse rate. The amount of ENaC b in urine is supposed to reflect the activity of sodium transport via the ENaCs, just as u-AQP2 reflects the functional status of the AQP2 water channels (6). Our analyses showed that the assay has a satisfactory reliability.…”
Section: Discussionmentioning
confidence: 70%
“…The degree of water transport via AQP2 is reflected by the level of urinary excretion of AQP2 (u-AQP2) (6). Correspondingly, the sodium transport via ENaCs is supposed to be reflected by the level of urinary excretion of the b-fraction of ENaC (u-ENaC b ).…”
Section: Introductionmentioning
confidence: 99%
“…As urinary AQP2 excretion is very low compared to the total AQP2 in the kidney (E3%), it may not reflect intrarenal changes in the protein. Nevertheless, a positive correlation has been found recently between the maximum changes in the urinary excretion of AQP2 and the maximum changes in plasma vasopressin in healthy subjects (Pedersen et al, 2001) (Figure 1b).…”
Section: Renal Consequences Of a High Level Of Vasopressin In A Healtmentioning
confidence: 70%
“…94 Urinary AQP2 is a commonly used assessment of AQP2 membrane targeting because it has been shown to reflect the physiologic response to VP in the CD. 95 This suggests that prostanoid-induced AQP2 membrane targeting is also observed in humans, which increases the clinical relevance of these findings.…”
mentioning
confidence: 73%